The animic dimension of law: a preliminary approach from analytic psychology - Mastro Puccio, Fernando del (2016)
This paper presents a proposal of interdisciplinary approach between analytic psychology and law. From the basis of Carl G. Jung’s theoretical framework, we argue that the law is animated by psychic contents of archetypical nature, which shape the way in which humans relate with rules and authority and impact how we regulate as a society. The paper introduces myth interpretation as a means to comprehend that animic dimension of law and describes the concepts, techniques and cares that should guide the analysis. An interpretation of the fall of Adam and Eve is conducted as an example of the proposed interdisciplinary approach. The analysis leads us to argue that the psychic tendency to separate the inner self from the outer self, with the relegation of the former, derives in the domination of the masculine over the feminine and in a relationship characterized by distance and fear between humans and the authority. The regulation that arises from that context is one also marked by separation, fear of sanctions and is focused on the external behavior. The image of Jesus is thus presented as compensatory one since it tends to the reunion of the inner with the outer and of the feminine with the masculine, which derives in a regulation substantially different from that of the Old Testament.